Efficacy of immune checkpoint inhibitors alone or in combination with chemotherapy in NSCLC harboring ERBB2 mutations - Saalfeld, Felix; Wenzel, Carina; Christopoulos, Petros; Merkelbach-Bruse, Sabine; Reissig, Timm M.; Laßmann, Silke; Thiel, Sebastian; Stratmann, Jan A.; Marienfeld, Ralf; Berger, Johannes; Desuki, Alexander; Velthaus, Janna-Lisa; et al. (Journal of thoracic oncology, 2021)
Introduction - In contrast to other driver mutations, no targeted therapies have yet been approved in ERBB2-mutated NSCLC (HER2mu NSCLC). Nevertheless, several compounds have revealed promising early efficacy data, which need to be evaluated in the context of current standard approaches. Although data on the efficacy of immune checkpoint inhibitors (ICIs) in second or subsequent lines of treatment remain limited and conflicting, there are virtually no data on patient outcome under ICI/platinum-doublet combinations in the first-line setting. - Methods - We retrospectively evaluated outcomes of patients with HER2mu NSCLC treated with ICI alone or in combination with chemotherapy within the German National Network Genomic Medicine Lung Cancer consortium by means of overall response rate (ORR), progression-free survival (PFS), and overall survival (OS). - Results - ICI either in combination with chemotherapy or as monotherapy was applied as first-line treatment in 27 patients, whereas 34 received single-agent ICI in second or subsequent lines. Patient characteristics were in line with previously published data. In treatment-naive patients receiving ICI in combination with chemotherapy, the ORR, median PFS, and OS rate at 1 year were 52%, 6 months, and 88%, respectively. In second or subsequent lines, ICI monotherapy was associated with an ORR of 16%, a median PFS of 4 months, and a median OS of 10 months. - Conclusions - ICIs are effective as monotherapy and in combination with platinum-doublet chemotherapy. Therefore, ICI-based treatments may be found as the current standard of care and benchmark for targeted therapies in HER2mu NSCLC.
Gesehen am 16.12.2021